2022
DOI: 10.3389/feduc.2022.846223
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers’ Attitudes Toward Students With Behavioral Difficulties: Associations With Individual and Education Program Characteristics

Abstract: Teachers’ belief toward students with special educational needs (SEN) in the regular classroom is a condition that may influence the implementation of inclusive education. Nevertheless, some studies suggest that teachers’ attitudes or self-efficacy beliefs toward students with behavioral difficulties (BD) are quite negative, but much less emphasis has been placed on the factors and mechanisms contributing to these attitudes. This study investigates associations between pre-service teachers’ (PT) attitudes towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our research findings showed relatively positive attitudes among pre‐service teachers. This result echoes those of Massé et al (2022), who asserted that attitudes among pre‐service teachers were ‘globally somewhat positive’.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our research findings showed relatively positive attitudes among pre‐service teachers. This result echoes those of Massé et al (2022), who asserted that attitudes among pre‐service teachers were ‘globally somewhat positive’.…”
Section: Discussionsupporting
confidence: 86%
“…It may be the case that the more knowledge pre-service teachers have, the more insecure and the less confident they feel in their abilities to work with and manage students with special needs (Ohan et al, 2008). This result is concerning (Massé et al, 2022), especially since the results of the current research showed that attitudes can be predicted by the course on inclusive education. Therefore, course curricula need to be more specific, not only in theoretical terms but also practically, so that preservice teachers possess the basic competencies needed to be inclusive teachers.…”
Section: Discussionmentioning
confidence: 68%
“…Evidence shows that to be effective, teachers should have sufficient knowledge about the best practices in teaching and of adapted instruction for LSENs, wherein positive attitude is most significant in creating an effective inclusive classroom. Additionally, in inclusive education, there are three groups of teachers, such as the keen, but anxious, beginners who are identified mostly as pre-service teachers with positive attitudes but are worried about their efficacy in inclusion; positive doers who are identified mostly as experienced teachers who struggle with the challenges met in inclusion; however, they maintain their positive attitudes; and resisters who are identified as the experienced teachers are resistant to inclusion (Massé et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more researchers have focused on exploring pre-service teachers' attitudes and beliefs before and after training programs, for the purpose of determining how to improve the programs and courses that prepare pre-service teachers (Li, 2016). For instance, teachers' attitudes and self-efficacy play a significant role in their pedagogical choices on whether and exactly how to incorporate information and communication technologies in their training (Pozas et al, 2022); on how to deal with students with behavioural difficulties (Massé et al, 2022).…”
Section: Introductionmentioning
confidence: 99%